(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Construction and Demolition (C&D) wastes are generated through the demolition of concrete structures, and they are often discarded into the open area causing environmental problems. Various components such as bricks, concrete, steel, wood, etc., are generated through the demolition of structures. Perhaps the necessity of construction materials, especially aggregates, increases rapidly due to urbanization and industrialization. Construction activities mainly depend on natural resources as a source of raw materials, leading to ecological imbalance. So, the construction industries tend to depend on alternative materials as the source of aggregates in concrete production. Recycling C&D wastes and using them as aggregates will be a viable option to counteract the problems mentioned above. The recycled aggregates are broken fractions of C&D wastes with smeared cement particles adhered to on the surface of natural aggregates. In this study, recycled aggregates were collected from a 20-year- old demolished building at the university and recycled into fractions of 1.18 mm 2.36 mm and 10 mm 20 mm and replaced for both fine aggregates and coarse aggregates. However, the poor quality of recycled aggregates resulting from the presence of adhered mortar affects the properties of the concrete. Thus, this paper aims to improve the property of recycled aggregates through surface treatments. Though various treatments were developed either to remove or coat the adhered mortar surface on the recycled aggregates, this study uses microbes in conjunction with advanced mixing approach techniques to improve the quality of recycled aggregates and properties of the recycled aggregate concrete (RAC). This paper finds Feasibility of Utilization of Modified Recycled Aggregate in various construction work by study the different Literature review and articles